Conceptual design of a lightweight machine with variable control for texturing on concrete surfaces - Ojeda Poma, Alan Saul (2022)
In Peru, constructions are commonly built with cement and bricks, then proceed to decorate and embellish the walls using texturing. Currently, in Peru, this process is done in a traditional way where generally support tools are used such as trowels, rollers, and brushes, among others. As this process is done manually, the texturing is of lower aesthetic quality. Due to its geographic location, Peru is one of the countries that most often applies cement in its constructions, which makes it the most accessible and suitable material for applying textures to walls. Currently, there is no specific machine for texturing, so the conceptual design of a lightweight machine for texturing on concrete surfaces was proposed using the VDI 2221 design methodology, integrating a variable speed control system and display of parameters in real-time.